Proteolytic Processing of Connective Tissue Growth Factor in Normal Ocular Tissues and during Corneal Wound Healing - Robinson, Paulette M. (The Association for Research in Vision and Ophthalmology, 2012)
PURPOSE. Connective tissue growth factor (CTGF) is a fibrogenic cytokine that is up-regulated by TGF-β and mediates most key fibrotic actions of TGF-β, including stimulation of synthesis of extracellular matrix and differentiation of fibroblasts into myofibroblasts. This study addresses the role of proteolytic processing of CTGF in human corneal fibroblasts (HCF) stimulated with TGF-β, normal ocular tissues and wounded corneas. METHODS. Proteolytic processing of CTGF in HCF cultures, normal animal eyes, and excimer laser wounded rat corneas were examined by Western blot. The identity of a 21-kDa band was determined by tandem mass spectrometry, and possible alternative splice variants of CTGF were assessed by 5′ Rapid Amplification of cDNA Ends (RACE). RESULTS. HCF stimulated by TGF-β contained full length 38-kDa CTGF and fragments of 25, 21, 18, and 13 kDa, while conditioned medium contained full length 38- and a 21-kDa fragment of CTGF that contained the middle “hinge” region of CTGF. Fragmentation of recombinant CTGF incubated in HCF extracts was blocked by the aspartate protease inhibitor, pepstatin. Normal mouse, rat, and rabbit whole eyes and rabbit ocular tissues contained abundant amounts of C-terminal 25- and 21-kDa fragments and trace amounts of 38-kDa CTGF, although no alternative transcripts were detected. All forms of CTGF (38, 25, and 21 kDa) were detected during healing of excimer ablated rat corneas, peaking on day 11. CONCLUSIONS. Proteolytic processing of 38-kDa CTGF occurs during corneal wound healing, which may have important implications in regulation of corneal scar formation.